ANALISIS TUNDAAN DAN PANJANG ANTRIAN AKIBAT PENUTUPAN PALANG PINTU KERETA API JPL 241 SUMBERGEMPOL TULUNGAGUNG - Arditya Radiantama; Aji Suraji; Agus Tugas Sudjianto (LPPM Universitas Abdurrab, 2025)
A good transportation system can guarantee safety, smoothness, speed, punctuality and comfort for the community. The JPL 241 Sumbergempol intersection includes a level crossing with various activities such as markets, shops and universities around the road location. The meeting of two types of transportation infrastructure results in significant traffic flows. The aim of the research is to analyze volume, capacity, degree of saturation, delays and length of vehicle queues. The data collection method is by conducting a direct survey at the JPL 241 Sumbergempol location. The data analysis method uses the 1997 MKJI guidelines. The research was carried out for 2 days on Sunday and Monday with an observation duration of 16 hours starting at 06.00 - 22.00 WIB. Data collection methods using survey equipment and field survey forms include traffic volume data, train gate closure duration data, vehicle delay data, and vehicle queue length data. The results of the analysis of the maximum traffic flow volume occurred on Monday at 17:45-18:00, amounting to 1230 pcu/hour with an average traffic flow volume of 871 pcu/hour. The results of the capacity analysis on the road section were found to be 2419.3 pcu/hour with a degree of saturation of 0.72. The results of the traffic delay analysis showed that the total traffic delay was 7805 sec/pcu with an average traffic delay of 1561 sec/pcu. The results of the queue length analysis using drone video showed an average of 36.6 pcu or 989.7 m long.